2022
DOI: 10.1038/s41598-022-27145-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying vital nodes for influence maximization in attributed networks

Abstract: Identifying a set of vital nodes to achieve influence maximization is a topic of general interest in network science. Many algorithms have been proposed to solve the influence maximization problem in complex networks. Most of them just use topology information of networks to measure the node influence. However, the node attribute is also an important factor for measuring node influence in attributed networks. To tackle this problem, we first propose an extension model of linear threshold (LT) propagation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Moreover, Yu et al identified the key nodes from the perspective of entropy by using the impact of node clustering coefficient and the number of first and second-order neighbors on the node importance [16]. In addition, Wang et al proposed a novel communitybased method to identify a set of vital nodes for influence maximization in the attributed networks [17]. Finally, Jiang et al developed an attenuation-based supra-adjacency matrix (ASAM) modeling method to further evaluate the importance of the nodes by calculating the similarity between adjacent layers and the cross-layer networks [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yu et al identified the key nodes from the perspective of entropy by using the impact of node clustering coefficient and the number of first and second-order neighbors on the node importance [16]. In addition, Wang et al proposed a novel communitybased method to identify a set of vital nodes for influence maximization in the attributed networks [17]. Finally, Jiang et al developed an attenuation-based supra-adjacency matrix (ASAM) modeling method to further evaluate the importance of the nodes by calculating the similarity between adjacent layers and the cross-layer networks [18].…”
Section: Introductionmentioning
confidence: 99%